Digital and Social Inequalities: A Qualitative Assessment of the Impact of the Connecting Equality Program on Argentinean Youth - Benítez Larghi, Sebastián (2015)
This paper focuses on the ties between social and digital inequalities among Argentinean youth. It uses a qualitative approach to explore different aspects of the everyday lives of adolescents, such as sociability, leisure time and family use of Information and Communication Technologies (ICTs), in order to assess the impact of the Connecting Equality Program (Programa Conectar Igualdad, PCI) on reducing digital inequalities and fostering social inclusion. What were the existing conditions of access for students and their families when the PCI was first implemented? What influence does the implementation of the PCI have on the individual, family and scholastic appropriation of ICTs? How does the use of computers and the Internet vary among youth? Has this large-scale incorporation of netbooks in schools, and especially homes and free time changed it in any way? Does the appropriation of ICTs through student participation in the PCI contribute to material and symbolic social inclusion? In order to answer these questions, we compare the processes of ICT appropriation among lower and middle class adolescents, focusing on the distinctive uses and meanings assigned to computers and the Internet by boys and girls in their daily lives. For this purpose we analyze data collected through semi-structured interviews in two schools in Greater La Plata, Argentina during 2012. The main findings show that in terms of access, skills and types of use, the implementation of the PCI has had a positive impact among lower class youth, guaranteeing access to their first computers and promoting the sharing of knowledge and digital skills with family members. Moreover, evidence of more diverse and intense use of ICTs among lower class students reveals the development of digital skills related to educational activities. Finally, in terms of sociability, having a personal netbook enables access to information and cultural goods which are very significant in generating ties and strengthening identities and social integration